2015
DOI: 10.1002/lary.25260
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐assisted cartilage reshaping for protruding ears: A review of the clinical applications

Abstract: The success rate for ear reshaping achieved with LACR appears promising. The use of this noninvasive technique will increase in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…There are differing opinions on the choice of laser in laser-assisted cartilage remodeling. Holden et al 17 and Leclère et al 18 report that the 1540-nm erbium laser and 1064-nm Nd:YAG laser have a good effect and are more suitable for cartilage remodeling. According to our clinical observations, the energy produced by the laser and the depth of laser penetration are key points throughout the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There are differing opinions on the choice of laser in laser-assisted cartilage remodeling. Holden et al 17 and Leclère et al 18 report that the 1540-nm erbium laser and 1064-nm Nd:YAG laser have a good effect and are more suitable for cartilage remodeling. According to our clinical observations, the energy produced by the laser and the depth of laser penetration are key points throughout the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The ideal wavelength for cartilage reshaping is 1540 nm because the penetration depth matches the thickness of cartilage, thereby allowing for homogenous heat generation. 22 A systematic review of seven clinical series 22 utilizing LACR to correct a prominent ear revealed a similar degree of correction when compared with conventional techniques. The authors claim that LACR provides a smoother, more natural curvature than conventional techniques, but without the incisions and subsequent scarring.…”
Section: Management Optionsmentioning
confidence: 98%
“…Bu uygulamanın lokal veya genel anestezi altında yapılabileceği, uygulama esnasında soğutucu spreylerin kullanılmasının yanık oluşumunu engellediği ve minimal invaziv bir yöntem olduğu ileri sürülmüştür. 17 CO 2 lazer ile otoplasti ise önce cilt insizyonu yapılması ve sonrasında kartilaja lazer uygulayarak kulak kartilajının şekillendirilmesi gerekmektedir. Bu teknikte en önemli dezavantaj cilt insizyonunun yapılmasıdır.…”
Section: Tıpta Kullanılan Lazer Tipleriunclassified